Structural perfection of (Na0.5Gd0.5)MoO4:Yb laser crystals. (1st April 2015) - Kuz'micheva, G.M.; Kaurova, I.A.; Zagorul'ko, E.A.; Bolotina, N.B.; Rybakov, V.B.; Brykovskiy, A.A.; Zharikov, E.V.; Lis, D.A.; Subbotin, K.A.
Abstract: Czochralski-grown (Na0.5 Gd0.5 )MoO4 single crystals doped with different concentrations of Yb 3+ ions have been investigated by X-ray diffraction. The type and concentration of point defects (different Na:Gd ratios, vacancies in Mo and O sites), and, consequently, the real compositions of the investigated crystals have been determined. The presence of additional reflections (50%) for the (Na0.5 Gd0.5 )MoO4 :10%Yb crystal was revealed, indicating the symmetry reduction from space group I 41 /a to P 4 _ without any change in the unit cell parameters. Crystal refinement within the framework of space group I 41 / a revealed an increase in the unit cell parameters for both (Na0.5 Gd0.5 )MoO4 :3%Yb and (Na0.5 Gd0.5 )MoO4 :10%Yb crystals; it can be explained by the kinetic phase transition of order–disorder type caused by the cation ordering at the dodecahedral sites in the local regions of the crystals. The reasons for the possible symmetry reduction in scheelite family crystals are discussed.